Impact of Outcome-Based Education on Graduate Readiness in the Era of Globalization through International Benchmarking: Pengaruh Outcome-Based Education (OBE) terhadap Kesiapan Lulusan di Era Globalisasi Studi Benchmarking Internasional - Royani Royani; Rifqi Fahrudin; Audira Freya Syatifa; Eka Dian Astuti (ADI Pengabdian Kepada Masyarakat, 2025)
Outcome Based Education (OBE) is an educational approach that emphasizes the achievement of clear and measurable learning outcomes to ensure graduates possess competencies relevant to industry needs and global challenges. This study aims to analyze the impact of OBE implementation on graduate readiness to compete in the global arena through an international benchmarking study. The research method employed is a comparative study, examining OBE implementation in several countries, such as Australia, Singapore, and Finland, and comparing it with the current situation in Indonesia. Data were collected through literature reviews, education policy reports, and interviews with academics and industry professionals. The findings indicate that countries with well-established OBE practices tend to produce graduates who are more competitive in the global job market. Key factors contributing to the success of OBE include curriculum flexibility based on industry demands, competency-based assessments and strong collaboration between higher education institutions and the workforce. In contrast, Indonesia faces several challenges in implementing OBE, such as limited infrastructure, lack of training for educators, and a gap between higher education and industry requirements. Therefore, a more structured strategy is needed, including curriculum reform, improved teaching quality and strengthened partnerships with industry sectors. This study offers insights for policymakers and educational institutions to optimize OBE practices in order to enhance graduate competitiveness in the era of globalization.